Politik Hukum Depenalisasi bagi Penyalahguna Narkotika dalam Perspektif Kemanfaatan Hukum - Mochammad Ali Sadikin; Cokorde Istri Dian Laksmi Dewi; Anak Agung Gede Agung Indra Prathama (Warmadewa Press, 2025)
The problem and issues regarding narcotics are classic problems, but they are still a major obstacle in law enforcement and national development. By criminalizing drug addicts, it does not make them immediately abandon drug abuse and experience a deterrent effect. The policy in preventing drug abuse and illicit trafficking must use a preventive approach. The type of legal research used is normative legal research. This study uses qualitative data analysis applied descriptively. With the benefit theory approach, according to the author, there are various benefits achieved and the effectiveness of punishment behavior in the form of rehabilitation when overcoming the problem of drug distribution and abuse. The model of punishment for victims of drug use so far considers them as part of a criminal group, so that rehabilitative efforts are often neglected.